Comparison of Western Blot Technique with Microscopy and Culture for Diagnosis of Tuberculosis (Bangladesh Journal of Medical Microbiology, 2016)
Diagnosis of tuberculosis is usually done by microscopy for AFB and other tests. But each test has different limitation. This study was carried out to compare western blot technique with microscopy and culture for diagnosis of tuberculosis. Sputum and other samples were collected from 112 TB patients for bacteriological diagnosis by microscopy and culture for AFB. Serum samples were collected from 112 TB patients and 50 control subjects for detection of antibody response by western blot. For western blot analysis, Mycobacterium tuberculosis sonicate antigen extract was fractionated by electrophoresis on  polyacrylamide gel.  Western blot analysis revealed four polypeptides against which antibody response of study population were observed. The sensitivity of western blot was 73.21% which was higher than that of microscopy (63.39%) and culture (57.14%) for diagnosis of tuberculosis. The specificity of western blot was 92%.Bangladesh J Med Microbiol 2007; 01 (01):21-24